A novel splice-site mutation in ALS2 establishes the diagnosis of juvenile amyotrophic lateral sclerosis in a family with early onset anarthria and generalized dystonias. - Saima Siddiqi; Jia Nee Foo; Anthony Vu; Saad Azim; David L Silver; Atika Mansoor; Stacey Kiat Hong Tay; Sumiya Abbasi; Asraf Hussain Hashmi; Jamal Janjua; Sumbal Khalid; E Shyong Tai; et al. (PLoS ONE, 2014)
The diagnosis of childhood neurological disorders remains challenging given the overlapping clinical presentation across subgroups and heterogeneous presentation within subgroups. To determine the underlying genetic cause of a severe neurological disorder in a large consanguineous Pakistani family presenting with severe scoliosis, anarthria and progressive neuromuscular degeneration, we performed genome-wide homozygosity mapping accompanied by whole-exome sequencing in two affected first cousins and their unaffected parents to find the causative mutation. We identified a novel homozygous splice-site mutation (c.3512+1G>A) in the ALS2 gene (NM_020919.3) encoding alsin that segregated with the disease in this family. Homozygous loss-of-function mutations in ALS2 are known to cause juvenile-onset amyotrophic lateral sclerosis (ALS), one of the many neurological conditions having overlapping symptoms with many neurological phenotypes. RT-PCR validation revealed that the mutation resulted in exon-skipping as well as the use of an alternative donor splice, both of which are predicted to cause loss-of-function of the resulting proteins. By examining 216 known neurological disease genes in our exome sequencing data, we also identified 9 other rare nonsynonymous mutations in these genes, some of which lie in highly conserved regions. Sequencing of a single proband might have led to mis-identification of some of these as the causative variant. Our findings established a firm diagnosis of juvenile ALS in this family, thus demonstrating the use of whole exome sequencing combined with linkage analysis in families as a powerful tool for establishing a quick and precise genetic diagnosis of complex neurological phenotypes.